Seasonal Variation and Sources of Elements in Urban Submicron and Fine Aerosol in Brno, Czech Republic - Hana Cigánková; Pavel Mikuška; Jitka Hegrová; Petra Pokorná; Jaroslav Schwarz; Jozef Krajčovič (Aerosol and Air Quality Research)
Abstract Seasonal variation and sources of elements bound to urban aerosol were studied. Fine (PM2.5) and submicron (PM1) aerosol was collected at 2-week campaigns during four seasons in 2018. The total concentration of 21 elements accounted on average for 3.5% of the total PM2.5 mass concentration and 2.0% of the total PM1 mass concentration. Seasonal differences in the element concentrations in PM1 and PM2.5 were found. Most elements in both aerosol size fractions had a higher concentration in winter or autumn than in summer or spring. Enrichment factor analysis showed extremely highly enriched Cd, Sb and Se in both fractions. Positive matrix factorization (PMF) analysis revealed 3 sources (residential heating, resuspension and anthropogenic background) for PM1 and 3 sources (residential heating, resuspension and brake abrasion) for PM2.5 aerosol in Brno. In addition, health risk assessment of possibly toxic elements was calculated.